Programa Universidade para Todos (ProUni): mudanças e possibilidades na vida dos sujeitos bolsistas - Simões, Paulo Roberto Rodrigues (2011)
The present work studies and analizes the University for All agenda (ProUni), seeking to deepen the studies involving changes and possibilities on the person s life on the basis of higher education, in the context of Educational Policy. The main objective is to verify how, from the admission of the ProUni s scholarship students in different courses, whether a better possibility of social change in the lives of these individuals occured or not. It starts with the assumption that, access, retention and conclusion of higher education for the public served by ProUni, foster social changes that alter the expectations and possibilities in the lives of scholarship students. The research methodology prioritizes the multi-dimensional approach which allows us to receive the contributions of different knowledge areas. In that sense, goes beyond limits from possible disjunctions bettween subject and object, nature and culture, empirical and theoretical, considering the dynamism of the relation bettween the whole and the shares. This research is part of a lager project. It is about an interinstitutional research, called ProUni and social inclusion, financed by the Coordination Of Personnel Improvement Of Higher Education (CAPES), and the National Institute Of Educational Studies and Researches Anísio Teixeira (INEP), within the Education Observatory, which the goal is to evaluate the process of integration and social inclusion of the students served by ProUni aiming a emancipatory action. The study focuses not only on the results for themselves, but demonstrates the understanding of the relation between the bonds of particular actions and the context where these take place